Diagnostic challenges in primary brain stem glioblastoma multiform; a case report - Malik, Muhammad Taimur; Kazmi, Syed Jaffar; Turner, Scott (Interdisciplinary neurosurgery : Advanced techniques and case management, 2017)
Brainstem gliomas are rare form of primary brain tumors in adult and represent <2% of gliomas. Glioblastomas (GBM) are much less common in pediatric patients; adult GBM vary in presentation and response to therapy, and generally have a very poor prognosis. GBM is less common in the brainstem, comprising <2% gliomas and there is therefore limited data available to provide a standard of care. Here we present a case report of a patient who presented with aggressive primary pontine GBM. •This case report highlights the importance of diagnostic challenges in brainstem glioma in a patient.•It also emphasizes on the role of neuroimaging including MRI of the brain and histological findings from the biopsy specimen.•Aggressive diagnostic approaches should be instituted for early diagnosis of brainstem glioma